Use of the extraoral arch in the correction of class II, division 2, type C malocclusion - Loza Campos, Juan Carlos (2018)
This case report presents a 13 year old patient who underwent a class II division 2 type C malocclusion treatment with an extraoral headgear, regarding patient’s age and skeletal maduration stage at that moment. Th is article presents the use of extraoral forces and the skeletal, facial and dental changes that were finally achieved.